Legal Construction on The Abuse of New Synthetic Narcotics Based on The Early Warning System - Faisal Suparjo; Evita Isretno Israhadi (Indonesian Journal Publisher, 2026)
The development of New Psychoactive Substances (NPS) demonstrates dynamics far faster than the ability of the narcotics criminal law to respond. The narcotics regulatory model in Indonesia, which still relies on a positive list system or list of prohibited substances, gives rise to various normative issues, ranging from delays in criminalization, legal uncertainty, and weak public health protection. This situation demonstrates a structural gap between scientific developments, particularly pharmacology and toxicology, and the static construction of criminal law norms. The study aims to analyze the weaknesses of narcotics criminal law regulations regarding NPS and to formulate an alternative, more adaptive criminal law construction through the Early Warning System (EWS) approach. The research method used is normative juridical with a legislative, conceptual, and comparative approach, including a study of the Psychoactive Substances Act 2016. The results show that the list-based criminalization approach is no longer adequate to address the ever-changing nature of NPS. The EWS has the normative potential to be repositioned as the foundation for the formation of criminal policies based on risk and psychoactive effects, without neglecting the principles of legality and human rights protection. A comparative study shows that the effects-based generic prohibition model provides regulatory flexibility, although it still presents challenges in terms of evidence and oversight. This study concludes that integrating EWS into narcotics criminal law is a strategic step towards building a responsive, legitimate, and public safety-oriented NPS control system, while simultaneously encouraging the renewal of modern criminal law theory in Indonesia.